A "poet" in the military camp at Tilurium - Sanader, Mirjana (Array, 2013)
The paper deals with four funerary versified inscriptions from Tilurium that mention deceased soldiers of the VII legion. It is presumed that in Tilurium was the "poet" or few of them who invented the verses for the Tilurian stelae or compiled the already known verses from sepulchral poetry all around the Empire and put them into the inscription.